N-fertilization for transplanted rice in combination with green manuring on acid sulfate soil - Tran, Thi Bang Tam; Nielsen, Jens Moller; Murty, V.V.N.; Koga, Kiyoshi; Sumitra Poovarodom; The Government of Sweden (Bangkok : Asian Institute of Technology, 1992)
The experiment was conducted at experiment field of Asian Institute of Technology, Bangkok, Thailand. The purpose of the study is to apply models of diagnosis, yield prognosis, and therapy in modern fertilization system with green manure (Sesbania rostrata) on acid sulfate soil for transplanted rice. Data analysis based on the chemical composition of young rice plant was used in order to: - Study relationship between the concentration of various nutrients at early stage of the growth (at selected 3 g/hill DMw) and final grain yield. - Test possibility of application of the basic models of fertilization system which were developed by Prof. J.M. Nielsen (DANIDA project) for lowland rice in Southeast Asia. - Study effect of Sesbania as a green manure on grain yield and on concentration of various nutrients in young rice plant. The experimental area, consisting of 12 treatments with 3 replications arranged randomly in the complete block design, was divided into two half. On one half of the area was incorporated with Sesbania. The plots with and without green manuring were applied with different levels of N fertilizer as basal dressing and as top dressing. Concentration of N, P, K, Ca, Mg, Na, Mn, Cu, and Zn in the taken plant samples was determined and used to evaluate and control nutritional status of the plant and to predict expected final yield. The agreement between results of the present and previous studies in respect to relationships between increasing N application and N concentration as well as concentration of other nutrients in plant (synergism or antagonism), relationship between predicted and actual final yield, relationship between varying concentration of N and other nutrients by supply additional N fertilizer in order to obtain desired grain yield with optimal chemical composition in plant, were showed in the study. Thus, the study was another evidence for the reliability and applicability of the general model.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1992
Keywords: Rice -- Planting; Fertilizers